Utilizing a Baculovirus/Insect Cell Expression System and Expressed Protein Ligation (EPL) for Protein Semisynthesis. Issue 1 (19th January 2022) - Butts, Marie; Chu, Nam
Abstract: Protein semisynthesis has been used for the chemoselective linking of synthetic peptides and recombinant protein fragments to generate complete native proteins in good yield. The ability to site‐selectively incorporate multiple post‐translational chemical modifications (PTMs) into proteins via this approach shows great potential for enhancing understanding of the molecular basis of protein function and regulation. Protein semisynthesis, however, often requires high expression efficiency of the recombinant protein fragments (i.e., high expression yield and ability to preserve protein biological functions), which can be hard to achieve for some human enzymes when using bacterial expression systems. Here, we describe how to use a baculovirus/insect cell expression system and a protein semisynthesis strategy known as expressed protein ligation (EPL) to produce workable levels of proteins of interest containing site‐specific chemical modifications. The protocol provides detailed guidance for generating protein C‐terminal thioesters for use with the EPL reaction, performing the EPL reaction, and purifying the protein ligation product. We exemplify the protocols by generating protein kinase Akt1 with site‐specific phosphorylations installed into its C‐terminal tail, for kinetic kinase assays. We hope these methods will help increase the use of protein semisynthesis for elucidating the post‐translational regulation of human enzymes involved in cell signaling. © 2022 Wiley Periodicals LLC Basic Protocol 1 : Generation of the N‐terminal protein of interest (POI) fragment containing a C‐terminal thioester moiety Basic Protocol 2 : Expressed protein ligation (EPL) of the protein thioester with a synthetic peptide and purification of the protein ligation product Basic Protocol 3 : Semisynthesis and biochemical analysis of site‐specifically phosphorylated Akt1